Aerosol-UA satellite mission for the polarimetric study of aerosols in the atmosphere. (June 2021) - Syniavskyi, Ivan; Oberemok, Yevgen; Danylevsky, Vassyl; Bovchaliuk, Andrii; Fesianov, Ihor; Milinevsky, Gennadi; Savenkov, Sergey; Yukhymchuk, Yuliia; Sosonkin, Mikhail; Ivanov, Yury
Highlights: Pre-flight calibration model of scanning and multispectral imaging polarimeters has been developed and updated for the Aerosol-UA satellite mission for atmospheric aerosol study. The multispectral imaging polarimeter model error of degree and azimuth of linear light polarization are estimated as 0.6% and 0.2°. In-flight photometric calibration of the Aerosol-UA instruments is discussed. Aerosol-UA data processing approach is based on GRASP algorithm. Abstract: We discuss the current state of the Ukrainian space project Aerosol-UA, which aims to provide data on the aerosol spatial distribution and microphysics in the Earth's atmosphere. The Aerosol-UA remote sensing concept is based on measurements from the multispectral Scanning Polarimeter (ScanPol) and the MultiSpectral Imaging Polarimeter (MSIP) on board the Yuzhnoe satellite (YuzhSat) platform. The ScanPol instrument is intended to measure intensity and polarization state of the light scattered by the Earth surface and atmosphere in the six spectral bands in the range from 370 to 1620 nm. The MSIP consists of five optical units and is intended to measure intensity and polarization state of the scattered light in the eight spectral bands in the range from 410 to 910 nm. The MSIP includes three polarimetric units (three spectral bands) and two radiometric units (eight spectral bands). These two Aerosol-UA instruments combined provide multi-angular measurements of the Stokes parameters of scattered radiance from the same scene. With the onboard calibration devices, the ScanPol allows the instruments to cross-calibrate as the fields-of-view of the two instruments are partly overlapped. We developed a polarimetric model for the instrument's pre-flight calibration and calibration procedure, based on that model. The model demonstrated good validity with the MSIP 555P nm polarimetric unit calibration experiment, and the errors of degree and azimuth of the linear light polarization were estimated at 0.6% and 0.2°, respectively. We considered details of the ScanPol pre-flight and in-flight radiometric and polarimetric calibration. The in-flight calibration set is used to perform polarized radiation calibration, depolarized radiation calibration, black body calibration, and radiometric calibration of the ScanPol. We discuss the ScanPol in-flight calibration with the solar diffuser plate, including the Spectralon flat diffuser plate and alternative possibilities. Vicarious methods, such as Rayleigh scattering, test sites, and Moon observations were considered for MSIP calibration. The data processing approach is also described in this paper.